Design and Experimental Study of a 3D-Printed Wing with a Morphing Trailing Edge - Pinho, João Correia de (2023)
In recent years, the interest in morphing technologies has been continuously growing. Many designs have been developed, but some are very complex to manufacture. The main goal of this dissertation is to present the development of a wing design with a morphing trailing edge that is easy to manufacture and control while allowing the execution of appropriate aerodynamic studies in a wind tunnel. Using computer-aided design and 3D (Three-dimensional) printing, a wing that is simply controlled with easy-to-use hardware is developed, manufactured, and studied using flow visualization and force acquisition. The whole developing steps are described in detail, as well as all the calibration processes of the required equipment to reproduce the final result, in order to enable others to proceed with further investigation using the present design. Considering initial studies, flow visualization showed that the presence of curvature delays stall when compared to the non-deflected configuration, where flow separation starts right at the leading edge. Also, the increase in deflection translates into an increase in the size of the wake, but not having a significant impact on the location of flow separation. In terms of force measurements, curvature plays an important role regarding lift enhancement, as well as substantially delaying wing stall when combining angle of attack with no flap deflection with trailing edge deflection. This design will allow for a wide range of studies to be performed, such as comparisons with conventional flap configurations to verify the performance of both systems, but also the study of unsteady conditions, including the dynamic motion of the trailing edge deflection, which can offer insights concerning aerodynamic surfaces design.